The Spaces of Others – Heterotopic Spaces: Practicing and Theorizing Hospitality and Counter-Conduct beyond the Religion/Secular Border - Wyller, Trygve; Heimbrock, Hans-Günter; Wyller, Trygve; Knauß, Stefanie; Sander, Hans-Joachim; Sander, Hans-Joachim; Pezzoli-Olgiati, Daria; Kreinath, Jens; Villadsen, Kaspar (Research in Contemporary Religion (RCR)., 2016)
Angaben zur beteiligten Person Heimbrock: Dr. päd. Hans-Günter Heimbrock ist Professor für Praktische Theologie am Fachbereich Evangelische Theologie der J. W. Goethe Universität Frankfurt a. M.